The Effect Analysis of Religiosity, Financial Literacy, and Islamic Financial Planning on The Performance of SMEs - Rilia Putri; Rahmat Mulyana; Nurul Hilmiyah (Eduvest - Journal of Universal Studies, 2024)
SMEs (Small and Medium Enterprises) serve as the backbone of the Indonesian economy, in a country with the world's largest Muslim population. Therefore, further analysis is needed regarding the factors influencing the performance of SMEs in an effort to maximize the country's revenue. This research aims to examine the relationship between religiosity, financial literacy, and Islamic financial planning on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the Greater Jakarta area (Jabodetabek). This study employs a quantitative approach using the Structural Equation Model Partial Least Square (SEM-PLS) with primary data collected through an online purposive sampling technique from 113 MSMEs in Jabodetabek. The performance of MSMEs is significantly influenced by religiosity, Sharia financial literacy, and Islamic financial planning. Religiosity has a significant impact on Sharia financial literacy and Islamic financial planning. Sharia financial literacy affects Islamic financial planning significantly.